Implications of Chemical-Thermal enhanced oil recovery methods in shale reservoirs. Issue 1 (1st January 2021) - Jing, Huang; Davarpanah, Afshin
Abstract: Recent advancement in enhanced oil recovery techniques has given petroleum industries the chance to find optimum solutions to recover remained oil from hydrocarbon reservoirs. This paper aims to experimentally investigate the profound impact of reservoir characteristics such as permeability and pressure drop and foams properties such as foam quality and foams resistance factor in enhanced oil recovery processes. Therefore, a hybrid recovery technique containing a thermal recovery method (carbon dioxide) and a chemical method (foam injection) with different brine concentrations was performed to enhance the oil recovery factor. Consequently, after brine injectivity, foam injection has provided the highest recovery factor among other scenarios in shale reservoirs. Permeability increase has caused to increase in the resistance factor as the fluid mobilization is increased in the porous media. Therefore, for 80% of foam quality, the resistance factor is about 7.5, while for 40%, foam quality is about 5 at the permeability of 10mD.